Sleep disturbance has the largest impact on children's behavior and emotions - Matsuoka, Michiko; Matsuishi, Toyojiro; Nagamitsu, Shinichiro; Iwasaki, Mizue; Iemura, Akiko; Obara, Hitoshi; Yamashita, Yushiro; Maeda, Masaharu; Kakuma, Tatsuyuki; Uchimura, Naohisa (Frontiers in Pediatrics, 2022)
Objective Children's behavior and emotions are affected by sleep disturbances, the parent-child relationship, media viewing time, and the social status of parents and caregivers. We conducted a questionnaire survey to identify the factors that have the greatest impact on children's behavior and emotions and how these factors relate to each other. Methods A parental questionnaire survey was performed at a public elementary school. The questionnaire comprised questions on the family environment (e.g., family structure, media and game exposure, after-school lessons, and caregiver's work schedule) and physical information, the Strengths and Difficulties Questionnaire (SDQ), the Children's Sleep Habits Questionnaire (CSHQ), and the Pittsburgh Sleep Quality Index (PSQI) for parents' sleep condition. A path diagram was drawn to hypothesize the complex interrelationships among factors, and structural equation modeling was used to estimate the path coefficients. Result We identified several factors that significantly affected the SDQ score. The CSHQ total score had the largest impact, followed by after-school lessons, single-mother families, and children's sex. In addition, several indirect pathways that led to the CSHQ score (i.e., a pathway from time spent watching television to CSHQ score via children's bedtime and a pathway from single-mother family to CSHQ score via PSQI total score) significantly affected the SDQ score. Conclusion Children's sleep habits that were influenced by several environmental factors had the greatest impact on children's behavior and emotions, which suggested that children's behavioral problems can be improved by interventions focused on sleep habits, such as sleep hygiene instructions.